Influence of carbon type and carbon to nitrogen ratio on the biochemical methane potential, pH, and ammonia nitrogen in anaerobic digestion - Yongjun Choi; Jeongwon Ryu; Sang Rak Lee (Journal of Animal Science and Technology, 2020)
Organic waste used as a feedstock in the anaerobic digestion (AD), it includes carbon and nitrogen. Carbon and nitrogen have an effect on the various digestive characteristics during AD, however, the study is rare about those of the interaction. This study investigates the influence of carbon type and carbon to nitrogens (C/N ratios) on the AD characteristics of organic waste. Experimental treatments involved a combination of three carbon types with three C/N ratios. The AD tests were carried out using a 125-mL serum bottle at a constant temperature of 37°C and moisture 95% for 18 days. Degradation pattern shows the difference among three-carbon treatments, the starch group was faster than other groups. Maximum methane production date was similar between starch (9.96 ± 0.05 day) and xylan group (10.0 ± 0.52 day), those of the cellulose group (14.6 ± 1.80 day) was slower than other groups (p < 0.05). The lag phase was only affected by the carbon type (p < 0.05). Ammonia nitrogen was mainly affected by nitrogen concentration regardless of carbon type (p < 0.05). This study showed that xylan is useful as feedstock in order to decrease the lag phase, and it showed that ammonia was independently affected by the nitrogen concentration.